2020
DOI: 10.5194/egusphere-egu2020-8476
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Antarctic Atmospheric River Climatology and Impacts

Abstract: <p>Atmospheric rivers, broadly defined as narrow yet long bands of strong horizontal vapor transport typically imbedded in a low level jet ahead of a cold front of an extratropical cyclone, provide a sub-tropical connection to the Antarctic continent and are observed to significantly impact the affected region’s surface mass balance over short, extreme events. When an atmospheric river makes landfall on the Antarctic continent, their signature is clearly observed in increased downwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 217 publications
(458 reference statements)
1
19
0
Order By: Relevance
“…MERRA-2 3 hourly single level and pressure level data are available via the Global Modeling and Assimilation Office (Global Modeling and Assimilation Office (GMAO), 2015a; Global Modeling and Assimilation Office (GMAO), 2015b). The code for the AR detection algorithm discussed in this study is publicly available (Wille, 2020). The SLP data associated with each SOM node and the dates from MERRA-2 assigned to each node and AR event is archived at the University of Colorado Boulder (Baiman, 2022)…”
Section: Data Availability Statementmentioning
confidence: 99%
“…MERRA-2 3 hourly single level and pressure level data are available via the Global Modeling and Assimilation Office (Global Modeling and Assimilation Office (GMAO), 2015a; Global Modeling and Assimilation Office (GMAO), 2015b). The code for the AR detection algorithm discussed in this study is publicly available (Wille, 2020). The SLP data associated with each SOM node and the dates from MERRA-2 assigned to each node and AR event is archived at the University of Colorado Boulder (Baiman, 2022)…”
Section: Data Availability Statementmentioning
confidence: 99%
“…These bands frequently originate in the tropics or subtropics and then extend southward, carrying large quantities of water vapour (Ralph et al, 2004;Zhu & Newell, 1998). Due to the significant intrusions of warm moist air, ARs landfalling in coastal Antarctica contribute to heavy snowfall, accounting for about 70% to 80% of the surface mass balance (SMB) and also affect melt processes in the ice sheet (Bozkurt et al, 2018;Gorodetskaya et al, 2014;Wille et al, 2019). Wille et al (2021), in their Antarctic-wide climatological analysis of ARs from 1980-2018, showed a significant increase in the number of ARs across DML.…”
Section: Introductionmentioning
confidence: 99%
“…Future variations in the snowfall are expected to follow the Clausius-Clapeyron relation, but remain largely uncertain. Currently, the SMB is driven mainly by variations in heavy precipitation events (Turner et al, 2019), in particular by Atmospheric Rivers (ARs) (Wille et al, 2021).…”
mentioning
confidence: 99%
“…ARs are atmospheric water vapor transport events that are rare but contribute significantly to the exchanges between mid and high latitudes (around 90% of meridional water vapor transport is linked to ARs, (Nash et al, 2018)). Over Antarctica, they dominate the variability of snowfall (Gorodetskaya et al, 2014), but can also lead to rainfall and warm extremes through advection of warm air and increased downward longwave radiation from liquid-laden clouds (Wille et al, 2019), which will contribute negatively to the SMB.…”
mentioning
confidence: 99%